Membership management system - Loh, Kar Yan (2025)
This project presents the development of a Membership Management System (MMS) to address the inefficiencies associated with manual membership processes such as registration, renewals, and activity tracking. Organizations that rely on traditional methods face challenges including human error, operational delays, and difficulty maintaining member engagement. The proposed MMS automates these processes, significantly reducing administrative workload and enhancing data accuracy. Then, the system integrates multi-channel communication tools, including email, SMS, and push notifications, to improve communication between organizations and their members. This ensures timely updates on events, renewals, and payments, resulting in improved member satisfaction and engagement. Additionally, the MMS provides real-time data analytics and reporting, enabling organizations to monitor member behavior, financial contributions, and event participation, thus facilitating data-driven decision-making. Besides, a centralized database ensures the consolidation of membership data, preventing data fragmentation and supporting scalability as the organization grows. By automating routine administrative tasks and streamlining communication, the MMS enables organizations to focus on strategic goals while providing more efficient, secure, and scalable system for membership management. Ultimately, this system enhances the overall membership experience and improves operational efficiency and member retention.